PENGARUH PROGRAM DIET DM-DISC TERHADAP INDEKS MASSA TUBUH (IMT) PASIEN DIABETES MELLITUS TIPE 2 - Dewi " Andraini; Yesi " Hasneli; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractThis research was purposed to obtain the effect of DM-Disc diet program on the body mass index of the patients with Diabetes Mellitus type 2 which was using Quasi Experimental design. This research was conducted at Arifin Achmad Hospital Pekanbaru. There were 30 patients as the respondent in which there were 15 patients as the experimental group and 15 patients as the control group. The sampling technique was Purposive Sampling. The measuring instrument used were direct measurement tools that Digital scale and Gauges. The experimental group was given the DM-Disc diet program for 1 week. The analysis used was Univariate analysis in order to obtain the distribution of frequency and Bivariate analysis used Wilcoxon and Mann Whitney tests. The result of this research showed: Univariate: The loss of body mass index happened in experimental group which the means were 27.233 (pretest) and 27.067 (posttest) and the difference was 0.166. Bivariate: There was no significant difference between the value of body mass index after being given the DM-Disc diet program in experimental group and the value of body mass index in control group which was not given DM-Disc diet program with p value 0,901 > α (0,05), meaning that statistically, using the Mann Whitney test, DM-Disc diet program did not affect to the loss of body mass index. This is probably caused by the time of DM-Disc diet program’s implementation which was only 1 week. While the significant body mass index changing actually needs 3-6 months. Key words             : Body Mass Index, DM-Disc Diet Program, Patients with Diabetes gMellitus